2009
DOI: 10.1002/mawe.200800440
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of barium on the surface of nanothick chromium oxide films grown on the (110) molybdenum substrate

Abstract: electron spectroscopy and work function measurements were used to investigate adsorption of barium onto the surface of nanothick chromium oxide films grown on the (110) molybdenum substrate. We prepared smooth 3-monolayers (ML) thick pseudomorphic chromium oxide films and rough 2 -3 ML chromium oxide films carrying three-dimensional oxide nanoparticles (the Stranski-Krastanov (SK) surface morphology). The interaction of barium with chromium oxide films of both types was found to lead to barium oxide formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Recent experimental [10,11] and theoretical [12] studies have suggested that multilayer oxides on the order of 10 nm can also reduce the work function of a metal. The work function is reduced by the alteration of the buried metal-oxide interface rather than at the oxide-vacuum surface.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental [10,11] and theoretical [12] studies have suggested that multilayer oxides on the order of 10 nm can also reduce the work function of a metal. The work function is reduced by the alteration of the buried metal-oxide interface rather than at the oxide-vacuum surface.…”
Section: Introductionmentioning
confidence: 99%